The evolution of minimal residual disease: key insights based on a bibliometric visualization analysis from 2002 to 2022 - Yu, Zhengyu; Xie, Li; Zhang, Jing; Lin, Hua; Niu, Ting (Frontiers in Oncology, 2023)
Background: The topic of minimal residual disease (MRD) has emerged as a crucial subject matter in the domain of oncology in recent years. The detection and monitoring of MRD have become essential for the diagnosis, treatment, and prognosis of various types of malignancy. Aims: The purpose of this study is to explore the research trends, hotspots, and frontiers of MRD in the last two decades through bibliometric analysis. Methods: We employed Web of Science databases to carry out a bibliometric visualization analysis of research on 8,913 academic papers about MRD research from 2002 to 2022. VOSviewer, CiteSpace, RStudio, and a bibliometric online analysis platform were mainly used to conduct co-occurrence analysis and cooperative relationship analysis of countries/regions, institutions, journals, and authors in the literature. Furthermore, co-occurrence, co-citation, and burst analyses of keyword and reference were also conducted to generate relevant knowledge maps. Results: In the past 20 years, the number of MRD research papers has presented an overall rising trend, going through three stages: a plateau, development, and an explosion. The output of articles in the United States was notably superior and plays a dominant role in this field, and the Netherlands had the highest average citation per article. The most productive and influential institution was the University of Texas MD Anderson Cancer Center. Blood published the most papers and was the most cited journal. A collection of leading academics has come to the fore in the research field, the most prolific of which is Kantarjian HM. It was found that the application of MRD in “acute myeloid leukemia”, “acute lymphoblastic leukemia”, “multiple myeloma”, as well as the detection technology of MRD, are the research hotspots and frontiers in this domain. Furthermore, we analysed the co-citation network of references and found that the top 10 co-cited references were all associated with MRD in hematological malignancies. Conclusion: This bibliometric visualization analysis conducted a thorough exploration into the research hotspots and trends in MRD from 2002 to 2022. Our findings can aid researchers in recognizing possible collaborations, guiding future research directions, and fostering the growth of MRD detection and monitoring technologies.